2015
DOI: 10.21101/cejph.a4189
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physical Activity in Treatment of Paediatric Obesity

Abstract: The aim of the study was to compare the differences in anthropometric parameters, maximal oxygen uptake (VO₂max) and physical activity (PA) between groups of 146 obese boys and 128 obese girls. We tried to describe the relationships between changes in PA and changes in VO₂max, body fat, weight, waist circumference and hip circumference. We found statistically significant changes in VO₂max and waist circumference only in the group of boys and significant changes in VO₂max in the group of girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Therefore, it seems more justified to assess the secondary biochemical parameters of insulin resistance than the insulin concentration level itself. The diet-only intervention caused greater reductions in the levels of triglycerides (at the end of active intervention) and low-density lipoprotein cholesterol (at subsequent follow-up) [35]. Study results suggested that diet plus exercise interventions may produce a greater improvement in metabolic parameters, especially HDL, cholesterol than only diet interventions [33,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it seems more justified to assess the secondary biochemical parameters of insulin resistance than the insulin concentration level itself. The diet-only intervention caused greater reductions in the levels of triglycerides (at the end of active intervention) and low-density lipoprotein cholesterol (at subsequent follow-up) [35]. Study results suggested that diet plus exercise interventions may produce a greater improvement in metabolic parameters, especially HDL, cholesterol than only diet interventions [33,36].…”
Section: Discussionmentioning
confidence: 99%
“…Pastucha D et al compared the differences in anthropometric parameters, maximal oxygen uptake (VO2max) and physical activity (PA) between groups of 146 obese boys and 128 obese girls. The analyses showed significant increases in VO2max values in both groups of boys ( p = 0.00028) and girls ( p = 0.00012) [35]. Both groups also showed significant increases in the total amount of PA.…”
Section: Discussionmentioning
confidence: 99%